Cost-effectiveness of rituximab in addition to fludarabine and cyclophosphamide (R-FC) for the first-line treatment of chronic lymphocytic leukemia. Issue 5 (3rd May 2016) - Müller, Dirk; Fischer, Kirsten; Kaiser, Peter; Eichhorst, Barbara; Walshe, Ronald; Reiser, Marcel; Kellermann, Lenka; Borsi, Lisa; Civello, Daniele; Mensch, Alexander; Bahlo, Jasmin; Hallek, Michael; et al.
Abstract: The cost-effectiveness of rituximab in combination with fludarabine/cyclophosphamide (R-FC) for the first line treatment of chronic lymphocytic leukemia (CLL) was evaluated. Based on long-term clinical data (follow-up of 5.9 years) from the CLL8-trial, a Markov-model with three health states (Free from disease progression, Progressive disease, Death) was used to evaluate the cost per quality-adjusted life-year (QALY) and cost per life years gained (LYG) of R-FC from the perspective of the German statutory health insurance (SHI). The addition of rituximab to FC chemotherapy results in a gain of 1.1 quality-adjusted life-years. The incremental cost-effectiveness ratio (ICER) of R-FC compared with FC was €17 979 per QALY (€15 773 per LYG). Results were robust in deterministic and probabilistic sensitivity analyses. From the German SHI perspective, rituximab in combination with FC chemotherapy represents good value for first-line treatment of patients with CLL and compares favorably with chemotherapy alone.